Communication about Waste Intervention Perspective Study on the Pandawara Community - Rahman, Mila Amalia; Bakti, Andi Faisal; Hermansyah, Tantan (Jurnal Dakwah dan Komunikasi, 2024)
Indonesian have a habit of throwing rubbish carelessly. Waste really pollutes the environment and affects the global climate, Indonesia is the third country contributing plastic waste in the world in 2020. The government does not care about environmental issues. This research aims to determine the influence of a group or community on behavior change in terms of developing a healthy environment in society. The waste problem in Indonesia is difficult to deal with, throwing rubbish carelessly is the culture in Indonesia, regulations regarding waste in Indonesia are not enforced enough. According to the Ministry of Environment and Forestry, only 20% of Indonesian people care about waste. People are used to throwing rubbish carelessly, such as into rivers and beaches. Lack of knowledge about waste processing. The rules regarding waste are only normative. Researchers used descriptive qualitative research methods, as well as three paradigms in communicating change for development. First, Behavior Change Communication, Communication for Social Change, Advocacy Communication. Pandawara Group uses social media to influence society. With the Pandawara Group going viral, many people were inspired and took part in cleaning rivers and beaches. The local government participates in supporting Pandawara activities. Many people are interested in this movement, but this is only temporary, without strict sanctions and self-awareness, the behavior of littering continues to occur